USULAN KONSEP KAUS KAKI CASUAL BERDASARKAN PREFERENSI TARGET PASAR PT SOKA CIPTA NIAGA MENGGUNAKAN CHOICE-BASED CONJOINT - Alya Fadhila, Hana
Soka Cipta Niaga is one of the halal fashion industry companies in Indonesia known for its socks. Soka faces challenges with inefficient production cycles, which have been linked to a lack of clearly defined target markets and insufficient understanding of consumer preferences. PT Soka has yet to employ market research approaches in product development, leading to potential misalignment with consumer expectations. The research commenced with market research using choice based conjoint (CBC) analysis to understand Indonesian consumers' preferences for socks. Five attributes were employed in the CBC experiment: color, pattern, model, material type, and length. Data collection was performed through judgmental sampling and snowball sampling by distributing online questionnaires, resulting in 203 respondents. The data were analyzed using the hierarchical Bayes (HB) estimation method to ascertain the preferences of Indonesian consumers for socks both individually and collectively. Based on the results of the analysis, it was found that the concept of socks according to the preferences of Indonesian consumers has dark colours, patterns, regular models (without toe separation), high ankle length, and cotton material. Market segmentation was conducted using latent class logistic regression which yielded three segments: youth essentials, chic and stylish, and timeless. The youth essentials segment was selected as the primary target market due to its largest number of individuals. The optimal price and consumer acceptable price range for the selected product concepts were determined using the Van Westendorp price sensitivity meter. The chosen product concept, preferred by the youth essentials segment, features neutral colours, patterns, regular models (without toe separation), high ankle length, and cotton material. Products can be sold in units or bundles, with unit prices ranging from Rp24.500-Rp40.000.